2008 IEEE 9th VLSI Packaging Workshop of Japan 2008
DOI: 10.1109/vpwj.2008.4762190
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable electronic systems for wearable and textile applications

Abstract: Assembly of electronic components on rigid and/or flexible printed circuit boards is today the customary way to fabricate electronic systems in stationary, mobile and automotive applications. On the other hand, many of the demands from emerging application fields like wearable and textile electronics cannot be met if with standard technologies. These fields have therefore become mayor drivers for the development of novel technologies. Among these 'stretchable electronics' have attracted much attention recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Nowadays, multifunctional portable electronic devices are being produced with rapid progress. [1d],45 However, the development of energy storage devices for these carry‐on devices is much slower compared with the electronic devices themselves. [4a],[41b],[41e],46 Even now, it remains a challenge to fabricate an energy storage device (such as supercapacitor) with the advantages of being light weight, flexible and having high performance.…”
Section: Compositing With Carbon Nanomaterials For High Performancmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, multifunctional portable electronic devices are being produced with rapid progress. [1d],45 However, the development of energy storage devices for these carry‐on devices is much slower compared with the electronic devices themselves. [4a],[41b],[41e],46 Even now, it remains a challenge to fabricate an energy storage device (such as supercapacitor) with the advantages of being light weight, flexible and having high performance.…”
Section: Compositing With Carbon Nanomaterials For High Performancmentioning
confidence: 99%
“…Pushparaj et al reported flexible energy storage devices based on nanocomposite paper. [46d] Cellulose was disolved into room temperature ionic liquid (RTIL) 1‐butyl‐3‐methylimidazolium chloride ([bmIm][45d]) using microwave irradiation and then was infiltrated into the vertically aligned thin‐walled multiwalled nanotubes (MWCNT) to form a uniform film of cellulose and [bmIm],[45d] embedding the MWCNT. The as‐obtained nanocomposite paper, which combined all three components (electrode‐spacer‐electrolyte) and formed the basic building unit in the resulting devices, was peeled from the substrate for using in the supercapacitor or lithium ion battery.…”
Section: Compositing With Carbon Nanomaterials For High Performancmentioning
confidence: 99%
“…One technological enabler is smart packaging using ultrathin flexible and even stretchable electronics ( Fig. 1.2.13) [29] and textile integration of electronics [30,31]. As this form-factor requirement puts the packaging technology very much on the forefront, system-package co-design is essential, especially in view of electromagnetic compatibility (such as battery-antenna-body coupling).…”
Section: Flex Stretch and Greenmentioning
confidence: 99%
“…It can be done using parts of apparels moving relatively one to another 19 . Integration can be done using technologies, which can create flexible and stretchable connections 21,25 , even some methods of ones used in textile industry can also be used in creation of connections, for example, embroidery. The latter is considered as most promising method for formation of resistive and inductive elements, connections etc., because it alters any textile in the least relevant way.…”
Section: Introductionmentioning
confidence: 99%